CHEMOTAXONOMIC ANALYSES AND CHEMICAL CONTENT OF SOME VARIETIES OF ONION (ALLIUM CEPA L.) - E. Karu; D.A. Zhigila; A. B. Mohammed; Ismaila, M.; U.A. Yuguda; M. U. Farouk (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
Eight (8) varieties of onions (Allium cepa) were characterized for total proteins using agarose gel electrophoresis (AGE-PAGE) and proximate chemical components. Total proteins were electrophorecally separated on 12% agarose gels by standard protocols. A total of 4 polypeptide bands were observed, of which 2 (25%) were polymorphic and 6 (75%) were monomorphic, with molecular weight ranging from 13.5 to 100 kDa. Results for the proximate analyses showed percentage contents of moisture 86.08±4.398, ash 4.45±1.386, fibre 15.01±3.184, lipids 7.44±1.101, protein 8.15±1.829 and carbohydrate 69.795±4.977. The Ex-Kudan variety gave the highest nutritional value while the Wuyan Bijimi variety gave the lowest. Dendrogram based on dissimilarity matrix using unweighted pair group method with arithmetic averages (UPGMA) separated all onion varieties into three main groups. Overall a low to medium level of genetic variability was observed for SDS-PAGE (single dimension). As AGE-PAGE alone did not reveal high level of genetic variability, hence 2-D gel electrophoresis along with other advanced type DNA markers and more number of onion varieties from all over the country are recommended for the future genetic evaluation. Our investigation will significantly support the classification, development, genetic evaluation and cultivation of onion in Nigeria.